μ+μ--Pair Production at Very Low Transverse Momentum in Ultra-Peripheral Heavy-Ion Collisions - ŞENGÜL, METİN (World Scientific Publishing Co Pte Ltd, 2025)
In recent works that are done at the STAR Collaboration, at small transverse momentum (p(perpendicular to)<150MeV/c) region, an excess e(+)e(-)-pair production has been observed in the peripheral collisions of gold-gold and uranium-uranium. Moreover, the ALICE Collaboration reported at low p perpendicular to a similar excess production of mu(+)mu(-)-pairs in the peripheral collisions of lead-lead. From the experiments for e(+)e(-)- and mu(+)mu(-)-pair productions at very low p(perpendicular to) that were done at the STAR and ALICE Collaborations, it is pointed out the coherent photon-photon interactions in ultra-peripheral hadronic heavy-ion collisions. In this study, we observed that muon pairs are mostly created in the transverse momentum domain of less than 0.15-GeV/c transverse momentum region like the electron-positron pairs in ultra-peripheral heavy-ion collisions. For this purpose, the impact parameter-dependent probability equations have been calculated for the STAR experiment Au+Au collisions and for the ALICE experiment Pb+Pb collisions at first. Then, we have calculated the mu(+)mu(-)-pair production cross-sections for those ions by using the Monte Carlo methods. Also, we showed the differential cross-sections for the Au+Au and Pb+Pb collisions as functions of transverse momentum p(perpendicular to), energy p(0) and invariant mass M of the produced mu(+)mu(-)-pairs for the given energy levels.
Keywords: QED; small transverse momentum; ultra-peripheral collisions; μ+ μ--Pair production